Structural insight into ligand binding interactions with DEN2 and DEN3 proteases / Pratheev Alagappan - Alagappan, Pratheev (2012)
Dengue is a serious disease which has re-emerged to become a global health burden. Currently, the only method deployed to manage this disease is by vector control. The increasing spread and severity of the dengue virus infection give emphasis to the importance of drug discovery strategies that could efficiently and cost-effectively identify potent drugs for development. In support of this requirement, several computational approaches were applied in this work. Initially structural comparison between the DEN2 homology model and DEN3 crystal structures and molecular docking studies of reference ligands to the DENV NS2B/NS3 serine protease were carried out. These reference ligands consist of reported competitive inhibitors and non-competitive inhibitors (4-hydroxypanduratin A, alpinetin, pinocembrin, pinostrobin and cardamonin). This study has provided some insights on possible binding interactions and comparison between the DEN2 homology model and DEN3 crystal structures where several differences with the interactions with the ligand binding residues have shown to be important for the protease inhibition.